The Influence of Budget Participation, Clarity of Budget Targets on Managerial Performance - Fitriasuri Fitriasuri; Siti Ratih Prisetya Dini (Quantitative Economics and Management Studies, 2023)
This study aims to determine and examine the partial and simultaneous effects on managerial performance of participation in budgeting and clear budget targets. In this examination the instrument utilized was a questionnire. This study employs a likert-shaped ordinal scale as the variable measurement scale. At PT Semen Baturaja (Persero) Tbk, there were 40 respondents in this study, with 20 managers and 20 supervisors each. SPSS 26 was used with the assistance of test revealed that managerial performance at PT Semen Baturaja (Persero) Tbk was influenced by partially budgeting participation, with a significant value of 0,000 < 0,05, while managerial performance there was unaffected by clear budget targets, with a significant value of 0,620 > 0,05. Additionally, the results of the research hypothesis test demonstrate that managerial performance was impacted simultaneously by budgeting participation and the clarity of budget targets at PT Semen Baturaja (Persero) Tbk with a value 0,000 < 0,05 and Fvalue > Ftable which was 29,545 > 3,25.